Latest Developments in Medical Robotics Systems - Küçük, Serdar (IntechOpen, 2021)
Medical robots are increasingly being used in the healthcare profession, particularly for surgical operations. Compared to traditional surgery techniques, robotic surgery results in smaller incisions, greater accuracy, and shortened recovery time. Medical robots can also be used to transport blood from one place to another, prepare substances in a hazardous environment, diagnose illnesses, care for patients, and more. As such, it is likely that robots will replace certain medical personnel in the future, leading to social consequences that are not yet fully understood. This book presents the latest developments in medical robotics and innovative designs of the future. It also examines current medical robotic systems and applications.